Student Perception toward the Use of Wordwall in Learning Descriptive Text: A Case Study at SMPN 1 Krian - Nafiza, Azza; Rakhmawati; Septianisari, Ima (ICONELT, 2024)
This research aims to explore students’ perceptions of the use of the Wordwall application media in studying text description material. Participants in this research were 36 class 7D students at SMP Negeri 1 Krian. The research method used is qualitative research using interview techniques for several students and observation of all participants. The research results show that the majority of students have positive perceptions of the use of Wordwall in learning. Students feel that this application helps them understand text description material more easily and pleasantly. Apart from that, using Wordwall also increases students’ learning motivation and makes the learning process more interactive. In conclusion, the Wordwall application is effectively used as a learning media in text description material, because it is able to increase students’ understanding and involvement in the learning process. It is hoped that these findings can be a reference for teachers in choosing innovative and effective learning media.